The Human Constraint How Business Leaders Can Embed Continuous Innovation, Conflict Resolution, and Problem Solving into Daily Practice. - Montgomery, Angela (Oxford : Productivity Press, 2024)
The Human Constraint is a business novel inspired by over 25 years of work in the field with a methodology that combines Deming's management philosophy and the Theory of Constraints to equip leaders with the knowledge, method, and tools to manage complex challenges and continuous innovation.
Intuition, Analysis, and Implementation -- The Challenge of Thinking Differently -- A New Verbalization for Transformation -- Never Lose Sight of the Goal -- Building a Conflict Cloud -- Challenging Our Mental Models and Seeing Others through Assumptions -- Opening Ourselves up to Change -- Beyond the Conflict Cloud: Connection and Transformation -- The Thinking Processes and Leadership -- The Thinking Processes and Free Choice -- About Intelligent Management -- Bibliography -- Index
Description based upon print version of record.
Keywords: Industrial management; BUSINESS & ECONOMICS / Decision-Making & Problem Solving; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Management